Physical-chemical characteristics of sweet cassava varieties - Patrick Rayan Gerino Teixeira (Revista Brasileira de Ciências Agrárias, 2017)
In order to evaluate the physical-chemical characteristics of nineteen sweet cassava varieties (Milagrosa, Paraguai, Maragogipe, IAC 576-70, Saracura, Amarela Viçosa, IAC Guaxupé, Manteiga, Aipim Furadinho, Calombo, BRS Dourada, Rosa, Manteigão, Pão da China, BRS Gema de Ovo, Colombo, BRS Eucalipto, Cacau Branca and BRS Rosada) this study was conducted at the State University of Southwest Bahia, in Vitoria da Conquista – BA. It was evaluated the pH, soluble solids, acidity, texture, cooking time, starch, amylose, amylopectin content, protein content and ash content of roots harvested at 12 months of age. We used a completely randomized design, with 3 repetitions. The data were submitted to analysis of variance and subsequently the treatment means were grouped by the Scott-Knott procedure, a 5% probability. There were differences between all the features, except for the ash content. Observed pH near neutral results in all varieties, with the highest values found in varieties Calombo and BRS Gema de Ovo. The Milagrosa variety had a higher percentage of soluble solids and higher texture. The IAC 576-70 stood out as the texture, the cooking time, the starch content and protein content. The highest percentage of amylose and amylopectin the lowest percentage was observed in the BRS Dourada.